2007
DOI: 10.1111/j.1525-1446.2007.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and Physical Abuse and Neglect as Manifestations of HIV/AIDS Stigma in Five African Countries

Abstract: Health care workers who encourage PLWA to disclose their HIV status must carefully consider the implications of encouraging disclosure in an environment with high levels of stigma, and must recognize the real possibility that PLWA may experience serious verbal and physical abuse as a consequence of disclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 15 publications
4
54
0
Order By: Relevance
“…On the individual level, recent studies have shown that disclosure of HIV positive status can result in increased violence experienced by women (Jansen van Rensburg 2007). On the community level, studies show that HIV positive women experience isolation from their communities once their status is discovered (Dlamini et al 2007). And on the national level, HIV can be criminalized through punitive laws that further enforce the stigmatization of people living with HIV (Burris and Cameron 2008).…”
Section: Discussionmentioning
confidence: 98%
“…On the individual level, recent studies have shown that disclosure of HIV positive status can result in increased violence experienced by women (Jansen van Rensburg 2007). On the community level, studies show that HIV positive women experience isolation from their communities once their status is discovered (Dlamini et al 2007). And on the national level, HIV can be criminalized through punitive laws that further enforce the stigmatization of people living with HIV (Burris and Cameron 2008).…”
Section: Discussionmentioning
confidence: 98%
“…This finding is supported by findings in similar studies in other African Countries that revealed both verbal and physical abuse of PLWHA at the family/community level. 14,33 Respondents also faced refusal of the family members to share cutleries, bedding or sleeping space, cooking utensils, toilet facilities, and seats with them. These findings show that despite the possibility of the family to support its members in all situations (including HIV and AIDS), there is still discrimination against PLWHA at the family level.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma and discrimination may manifest as verbal and physical abuse, neglect and isolation, for example, name-calling, separating utensils and denying access to services (Dlamini et al, 2007). HIV/AIDS affected children experience stigma and discrimination related to HIV/AIDSrelated illness and death of their parents.…”
Section: Growing Up In the Era Of Aidsmentioning
confidence: 99%